Lipophilic phytochemicals from banana fruits of several Musa species - Vilela, Carla (2021)
The chemical composition of the lipophilic extract of ripe pulp of banana fruit from several banana cultivars belonging to the Musa acuminata and Musa balbisiana species (namely 'Chinese Cavendish', 'Giant Cavendish', 'Dwarf Red', 'Grand Nain', 'Eilon', 'Gruesa', 'Silver', 'Ricasa', 'Williams' and 'Zelig') was studied by gas chromatography-mass spectrometry for the first time. The banana cultivars showed similar amounts of lipophilic extractives (ca. 0.4% of dry material weight) as well as qualitative chemical compositions. The major groups of compounds identified in these fractions were fatty acids and sterols making up 68.6-84.3% and 11.1-28.0%, respectively, of the total amount of lipophilic components. Smaller amounts of long chain aliphatic alcohols and α-tocopherol were also identified. These results are a relevant contribution for the valorisation of these banana cultivars as sources of valuable phytochemicals (ω-3 and ω-6 fatty acids, and sterols) with well-established beneficial nutritional and health effects.